Additional file 1 of The transfer of maternal antibodies and dynamics of maternal and natural infection-induced antibodies against coxsackievirus A16 in Chinese children 0–13 years of age: a longitudinal cohort study - Jiaxin Zhou; Yonghong Zhou; Kaiwei Luo; Qiaohong Liao; Wen Zheng; Hui Gong; Huilin Shi; Shanlu Zhao; Kai Wang; Qi Qiu; Bingbing Dai; Lingshuang Ren; et al. (figshare, 2022)
Additional file 1: Fig. S1. Time series and predicting epidemic magnitude of CVA16 activity in Anhua county during 2013-2016 (A) and that in Hunan province during 2009-2018 (B). Fig. S2. Participants’ included time in baseline and follow-up times (A) and the epidemic seasons of CVA16 activity during 2009-2018 in Anhua, Hunan province (B). Fig. S3. Distribution of maternal antibody titre transfer ratio against CVA16 for all pairs of neonate-mother (A) and positive mothers with antibody titre ≥8 (B). Fig. S4. The aggregated maternal titre specified transfer ratio. Fig. S5. Maternal antibody titre transfers efficacy against CVA16. Fig. S6. Transfer ratio trend with all pairs of mother-neonate. Fig. S7. Dynamic of seroprevalence, neutralization antibody titre by age for neonates using 16 as positive threshold. Fig. S8. Dynamic of neutralization antibody titre by age for neonates using full follow-up subset. Fig. S9. Dynamics of neutralization antibody titer by age for neonates stratified by maternal antibody levels. Fig. S10. Waning rate of maternal transmitted CVA16 antibody and natural infection induced antibody. Fig. S11. Age distribution and cumulative distribution of HFMD associated to CVA16 by clinical severity in Hunan province during 2009-2018 and Anhua county during 2013-2016. Table S1. Distribution of participants aged 1-9 years and sampling ratio. Table S2. Seasonality comparison between Anhua county and Hunan province. Table S3. Epidemic duration for CVA16 circulation in Anhua. Table S4. (a) Baseline characteristics of mothers and neonates in neonate cohort between participants and non-participants, selected participants and non-selected participants for CVA16 assay. (b) Baseline characteristics of neonates in neonate cohort between full follow-up participants and incomplete follow-up participants. Table S5. Comparison of baseline characteristics of 1-9 years old children between participants and non-selected objects through sampling, full follow-up and incomplete follow-up. Table S6. Seroprevalence and GMT of mothers and neonates at birth. Table S7. Sample size (n, %) for CVA16 antibody transfer ratio analysis. Table S8. Multivariate analysis with factors associated with neonates’ seropositivity, antibody titre at birth and transfer ratio. Table S9. Univariate analysis with factors associated with neonates’ seropositivity at birth. Table S10. Univariate analysis with factors associated with the transfer ratio of maternal antibody. Table S11. Univariate analysis with factors associated with neonates’ antibody titre at birth. Table S12. Sensitive analysis for multivariate analysis with factors associated with maternal antibody transfer ratio. Table S13. Sensitive analysis of median age of neonate with positive antibody. Appendix.
Keywords: Medicine; Biotechnology; Immunology; Cancer; Infectious Diseases; Computational Biology